Novel strategies for tumor radiosensitization mediated by multifunctional gold-based nanomaterials. (5th January 2023) - Wang, Ze; Ren, Xiaojun; Wang, Dongzhou; Guan, Lin; Li, Xingchen; Zhao, Yue; Liu, Annan; He, Liang; Wang, Tiejun; Zvyagin, Andrei V.; Yang, Bai; Lin, Quan
Abstract : In this review, we systematically summarize the recent progress of various new gold-based nanomaterials mediating radiosensitization and describe the mechanism. The challenges and prospects in the field were further discussed. Abstract : Radiotherapy (RT) is one of the most effective and commonly used cancer treatments for malignant tumors. However, the existing radiosensitizers have a lot of side effects and poor efficacy, which limits the curative effect and further application of radiotherapy. In recent years, emerging nanomaterials have shown unique advantages in enhancing radiosensitization. In particular, gold-based nanomaterials, with high X-ray attenuation capacity, good biocompatibility, and promising chemical, electronic and optical properties, have become a new type of radiotherapy sensitizer. In addition, gold-based nanomaterials can be used as a carrier to load a variety of drugs and immunosuppressants; in particular, its photothermal therapy, photodynamic therapy and multi-mode imaging functions aid in providing excellent therapeutic effect in coordination with RT. Recently, many novel strategies of radiosensitization mediated by multifunctional gold-based nanomaterials have been reported, which provides a new idea for improving the efficacy and reducing the side effects of RT. In this review, we systematically summarize the recent progress of various new gold-based nanomaterials that mediate radiosensitization and describe the mechanism. We further discuss the challenges and prospects in the field. It is hoped that this review will help researchers understand the latest progress of gold-based nanomaterials for radiosensitization, and encourage people to optimize the existing methods or explore novel approaches for radiotherapy.